2020
DOI: 10.1021/acs.est.0c05972
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Receptor Antagonism of Chemicals Extracted from Personal Silicone Wristbands within a Papillary Thyroid Cancer Pilot Study

Abstract: Research suggests that thyroid cancer incidence rates are increasing, and environmental exposures have been postulated to be playing a role. To explore this possibility, we conducted a pilot study to investigate the thyroid disrupting bioactivity of chemical mixtures isolated from personal silicone wristband samplers within a thyroid cancer cohort. Specifically, we evaluated TRβ antagonism of chemical mixtures extracted from wristbands (n = 72) worn by adults in central North Carolina participating in a case−c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 112 publications
1
16
0
Order By: Relevance
“…There are several studies that have used silicone wristbands to detect exposure to a variety of pesticides in humans. ,,,, Many of these may not be representative of our study population because they were focused on evaluating exposures in study participants that were either children or lived in agricultural areas. ,,, A recent study by our group used wristbands to measure exposure in an adult population with an overlapping geographic range of North Carolina counties over 7 days and also found that the most abundant pesticides were permethrin isomers …”
Section: Resultsmentioning
confidence: 99%
“…There are several studies that have used silicone wristbands to detect exposure to a variety of pesticides in humans. ,,,, Many of these may not be representative of our study population because they were focused on evaluating exposures in study participants that were either children or lived in agricultural areas. ,,, A recent study by our group used wristbands to measure exposure in an adult population with an overlapping geographic range of North Carolina counties over 7 days and also found that the most abundant pesticides were permethrin isomers …”
Section: Resultsmentioning
confidence: 99%
“…Most exposures included volatile and semi-volatile compounds measured using gas-chromatography (GC), including single-and triple-quadrupole mass spectrometers, with some studies leveraging electron capture detectors for increasing specificity towards halogenated compounds [60,67,71,72]. Only a few studies combined GC with HRMS, including time of flight (TOF) and Orbitrap mass spectrometers [61][62][63][73][74][75][76][77][78][79]. Of the studies using HRMS technologies, only 50% were untargeted, defined as methods that used data-driven approaches for signal detection, filtering, and annotation.…”
Section: Passive Sampling Devices For External Exposome Profilingmentioning
confidence: 99%
“…Although few studies focus on biological endpoints, recent applications have attempted to link PSD measurements to health outcomes, including DNA damage biomarkers [72], thyroid function [95], social behaviors in children [96], and respiratory-related disorders [62]. Interestingly, one study combined wristbands with effect-directed analysis (EDA) to identify wristband-captured exposures contributing to thyroid dysfunction [76]. In this study, extracted wristbands were tested using gene-reporter assays that evaluate thyroid disrupting bioactivity, providing a biological-based prioritization of compounds potentially contributing to adverse effects.…”
Section: Passive Sampling Devices For External Exposome Profilingmentioning
confidence: 99%
“…Although TC was once considered a relatively uncommon malignancy, in general, the incidence of TC has been increasing year by year due to various Ivyspring International Publisher potential factors including environmental contaminations [16,17]. Indeed, long-term, highquality registry data have revealed that the incidence of the disease has increased substantially over the past few decades in almost every country [11,18].…”
Section: Thyroid Cancer and Autoimmune Thyroid Diseasesmentioning
confidence: 99%